Conceal, don't feel - Calonita, Jen (Twisted tale., 2019)
In a retelling of Disney's "Frozen," Elsa has grown up as a princess in Arendelle always feeling like a huge part of her life is missing--only she cannot figure out what it is. When her parents die, Princess Elsa must answer the questions plaguing her, find out how to be a ruler, and fill in the missing memories of her childhood.